Sanitation Finance in Rural Cambodia - Robinson, Andy (World Bank, Washington, DC, 2014)
This document presents the findings of a study on sanitation finance in Cambodia conducted for the Water and Sanitation Program (WSP) with support from the Asian Development Bank (ADB). The overall objective of the assignment was to consider sustainable sanitation financing options with a focus on promoting access for the poorest. This guidance note contains an introduction on sanitation financing and subsidies, stating the cases for subsidies as well as some of their practical pitfalls. The study used data (as of late 2009) from two case studies of rural sanitation finance in Cambodia to illustrate the practical issues, sup-plemented by preliminary data from two sanitation marketing projects. The study also examined the potential use and effectiveness of (hardware) subsidies, conditional cash transfers (CCTs), and other financing approaches relevant for sanitation improvement. The document ends with recommendations for improved sanitation finance, including practical suggestions for sanitation programs in Cambodia. These recommendations bear particular relevance for the ADB's Second Rural Water Supply and Sanitation Sector Project, which commenced in 2010.